Алгоритми розпізнавання БПЛА за акустичним випромінюванням - Гісцев, А. Ю. (ХНУРЕ, 2023)
Algorithms for recognition of UAVs using acoustic systems designed for the detection of aircraft are considered. The advantages and disadvantages of this method are analyzed. It is shown that modern recognition methods and algorithms, implemented with the help of acoustic sensors, allow solving the problem of determining the coordinates of aircraf
Keywords: розпізнавання БПЛА